Assessing transgender and gender non‐conforming pedigree nomenclature in current genetic counselors' practice: The case for geometric inclusivity. Issue 6 (30th March 2020) - Sheehan, Elizabeth; Bennett, Robin L.; Harris, Miles; Chan‐Smutko, Gayun
Abstract: Healthcare professionals rely on national organizations for guidance; the National Society of Genetic Counselors (NSGC) and the National Comprehensive Cancer Network (NCCN) have differing guidelines for acceptable pedigree symbols to represent transgender patients and minimal recommendations for gender non‐conforming (GNC) patients. Inconsistency in accepted pedigree symbols to represent these patients is a barrier to providing them appropriate care. We assess variability in pedigree practice among genetic counselors and students, as well as reported education on serving the needs of the transgender and GNC communities, through a survey distributed through NSGC. Participants felt symbols similar to NSGC's (41.1%) and NCCN's (29.7%) recommendations for transgender patients are appropriate and emphasized a desire to affirm gender identity. We identified greater variability in symbols representing a GNC patient; 19.2% of participants selected 'other', explaining they were unsure of the appropriate choice. A high interest (99%) in further training demonstrates a recognition of education as an effective strategy for improving awareness and competency. Promotion of existing resources could help address the fact that 81% of participants were unaware of any standardized symbols used to represent transgender individuals. Creating affirming, standardized pedigree nomenclature is necessary for appropriate and consistent care.